Molecular architecture of mouse activating NKR-P1 receptors - Kolenko, Petr; Rozbeský, Daniel; Vaněk, Ondřej; Kopecký, Vladimír; Hofbauerová, Kateřina; Novák, Petr; Pompach, Petr; Hašek, Jindřich; Skálová, Tereza; Bezouška, Karel; Dohnálek, Jan (Journal of structural biology, 2011)
Receptors belonging to NKR-P1 family and their specific Clr ligands form an alternative missing self recognition system critical in immunity against tumors and viruses, elimination of tumor cells subjected to genotoxic stress, activation of T cell dependent immune response, and hypertension. The three-dimensional structure of the extracellular domain of the mouse natural killer (NK) cell receptor mNKR-P1Aex has been determined by X-ray diffraction. The core of the C-type lectin domain (CTLD) is homologous to the other CTLD receptors whereas one quarter of the domain forms an extended loop interacting tightly with a neighboring loop in the crystal. This domain swapping mechanism results in a compact interaction interface. A second dimerization interface resembles the known arrangement of other CTLD NK receptors. A functional dimeric form of the receptor is suggested, with the loop, evolutionarily conserved within this family, proposed to participate in interactions with ligands.
Keywords: Animals; buňky NK; sekvence aminokyselin; Spectrum Analysis, Raman; sekundární struktura proteinů; Molecular Sequence Data; molekulární sekvence - údaje; zvířata; Mice; Protein Structure, Secondary; X-Ray Diffraction; difrakce rentgenového záření; Killer Cells, Natural; Amino Acid Sequence; Ramanova spektroskopie; NK Cell Lectin-Like Receptor Subfamily B; lektinové receptory NK-buněk - podrodina B; myši